Spinal Muscular Atrophy Diagnosed by Newborn Screening - Matias Lopez-Chacon; Amber N Buehner; Vamshi K Rao (Pediatric Neurology Briefs Publishers, 2019)
A panel of experts representing academic centers, family foundations and pharmaceutical industry came together to formulate a treatment algorithm for infants diagnosed via newborn screening (NBS) with Spinal muscular atrophy (SMA).